Communication in Neuropalliative Care - Besbris, Jessica; Baker, Jessica; Kramer, Neha M. (Seminars in Neurology, 2024)
Serious illness communication needs are high among patients with neurological conditions, from the time of diagnosis to the end of life. This article will highlight unique needs among these patients, strategies for optimizing communication, and techniques to learn and teach these skills along the continuum of a career in neurology.
Keywords: serious illness conversations; prognostic uncertainty; road mapping; best case/worst case; shared decision-making; goals of care; serious neurological illness; goal-concordant care